Pengaruh Pengungkapan Corporate Social Responsibility dan Manajemen Laba Terhadap Agresivitas Pajak - Dea Herfiana; Bardjo Sugeng (Jurnal Riset Mahasiswa, 2021)
This study aims to test and analyze empirically the effect of Corporate Social Responsibility Disclosure and Earnings Management on Tax Aggressiveness in Automotive Sub Sector Manufacturing companies listed on the Indonesia Stock Exchange for the period 2014-2018. The factors tested in this study are Disclosure of Corporate Social Responsibility, Earnings Management and Tax Aggressiveness. The method used in this research is descriptive method and verification method. This study uses secondary data obtained from the website www.idx.co.id. The sample used in this study was using purposive sampling technique, so that the sample used in this study amounted to 5 (five) Automotive Sub Sector Manufacturing companies listed on the Indonesia Stock Exchange period 2014-2018. Testing research hypotheses using world test statistics (partial). The statistical analysis process uses SPSS 26 for windows. To determine the effect of Corporate Social Responsibility Disclosure and Earnings Management on Tax Aggressiveness, simple linear regression analysis, correlation analysis, and coefficient of determination are used. The results of this study indicate the Disclosure of Corporate Social Responsibility affects the Tax Aggressiveness with the percentage of influence of 33.9% and Earnings Management influences the Tax Aggressiveness with the percentage of influence of 20.4%.